The Impact of Intelligence (IQ) and Learning Styles on Mathematics Learning Motivation and Achievement in Secondary School Students - Hadi Prayitno; Imam Sujadi; Isnandar Slamet; Getut Pramesti (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2025)
This study aims to examine the influence of intelligence quotient (IQ) and learning styles on students’ learning motivation and mathematics achievement among tenth-grade high school students. The research employed a quantitative approach using an ex post facto design. A total of 83 students participated in the study, selected through a census sampling technique, as the entire population of tenth-grade students was included. Instruments used in this study included an IQ test, a learning style questionnaire (covering auditory, visual, and kinesthetic styles), a motivation questionnaire, and a mathematics achievement test. Data analysis involved instrument validity and reliability testing, classical assumption tests (normality and homogeneity), and multivariate analysis (MANOVA) to assess both the direct and interaction effects of IQ and learning styles on learning motivation and mathematics achievement. The results showed that IQ had a significant effect on mathematics achievement (p < 0.05), but no significant effect on learning motivation. Learning styles did not significantly influence either mathematics achievement or learning motivation. Furthermore, there was no significant interaction between IQ and learning styles in relation to either outcome. The coefficient of determination (R²) indicated that the model explained 26.3% of the variance in mathematics achievement and 16.5% of the variance in learning motivation. It can be concluded that IQ contributes to students’ success in mathematics, while learning motivation and performance are also shaped by other factors beyond IQ and learning styles. These findings highlight the importance of instructional strategies that consider students’ intellectual capacities along with affective and contextual factors